The development and demonstration of a multiple stage anaerobic digester for the treatment of high solids wastes - Loetscher, Lucas H., author; Sharvelle, Sybil, advisor; De Long, Susan, committee member; Davis, Jessica, committee member (Colorado State University. Libraries, 2018)
The semi-arid Great Plains of the central United States is home to numerous high-density, confined animal feeding operations (CAFOs) that utilize outdoor animal pens. These facilities generate a desiccated manure very different from the wastes generated from similar enclosed facilities in other parts of the country. These high-solids wastes present challenges to the conventional digestion systems commonly used on wastes with lower solids contents. Therefore, it was determined that there was a need in the industry for a new technological approach to improve feasibility of the digestion of these challenging wastes. A first principle design technique was applied to the conceptual design of an innovative technology better suited to such a challenging substrate. This system, named the CSU multiple-stage anaerobic digester (MSAD) technology, is a promising technical alternative to existing AD technologies. The CSU MSAD technology demonstrated the ability to overcome various limitations in previous anaerobic digestion technologies and ultimately demonstrated the ability to be used in the digestion of a wider variety of substrates. A demonstration-scale CSU MSAD system was constructed and operated for a duration of four months. The demonstration-scale equipment was constructed as a stand-alone mobile pilot lab that could function with various substrates and hydrolysis reactor configurations. In addition to the demonstration of the MSAD system on manure wastes, experiments were conducted on the digestion and inoculation of food wastes. Findings from these experiments indicated that substrate inoculation became less important as the digestion system operated for a longer duration. Inferring from these findings, it is expected that commercial MSAD digesters will not benefit from substrate inoculation after the system completes a successful startup process. An analysis of the existing state of the MSAD technology was completed based on review of previous research efforts. To prioritize future research efforts, a modified technology development risk analysis using qualitative scores was applied to development needs of the technology that currently have unknown and potentially risky outcomes. This approach has led to a series of recommended future development efforts for the commercialization of this technology.
Keywords: digestion; multiple stage digestion; leachate; biogas